2012
DOI: 10.1002/lary.22389
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β3 for the prevention of vocal fold scarring

Abstract: Administration of TGFβ3 before injury significantly suppressed scar formation and induced favorable restoration of extracellular matrices in the vocal fold lamina propria, resulting in much improved phonatory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…We also show that TGF-β3 is a less potent inducer of key profibrotic molecule expression and fibroblast-myofibroblast differentiation in human VFF, compared with TGF-β1 and TGF-β2; and that delivery of exogenous TGF-β3 during the acute injury phase modulates the inflammatory environment and reduces VFM scar formation in vivo . These findings corroborate and provide mechanistic support for a recent therapeutic trial using canine VFM (Ohno et al, 2012), as well as multiple reports in skin (Ferguson et al, 2009; McCollum et al, 2011; Shah et al, 1995; So et al, 2011), lip (Hosokawa et al, 2003) and OM (Ohno et al, 2011). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also show that TGF-β3 is a less potent inducer of key profibrotic molecule expression and fibroblast-myofibroblast differentiation in human VFF, compared with TGF-β1 and TGF-β2; and that delivery of exogenous TGF-β3 during the acute injury phase modulates the inflammatory environment and reduces VFM scar formation in vivo . These findings corroborate and provide mechanistic support for a recent therapeutic trial using canine VFM (Ohno et al, 2012), as well as multiple reports in skin (Ferguson et al, 2009; McCollum et al, 2011; Shah et al, 1995; So et al, 2011), lip (Hosokawa et al, 2003) and OM (Ohno et al, 2011). …”
Section: Discussionsupporting
confidence: 88%
“…Specifically, TGF-β1 and TGF-β2 are associated with fibrotic healing in adult wounds, whereas TGF-β3 is associated with regenerative healing in fetal wounds (Ferguson and O’Kane, 2004; Occleston et al, 2011; Shah et al, 1995; Whitby and Ferguson, 1991). Delivery of recombinant or therapeutically mutated TGF-β3 at the time of injury has been shown to reduce scar formation in skin (Shah et al, 1995; Waddington et al, 2010), lip (Hosokawa et al, 2003), oral mucosa (OM) (Ohno et al, 2011) and VFM (Ohno et al, 2012) in preclinical models, and recombinant TGF-β3 has demonstrated safety and efficacy in phase I and II human clinical trials (Ferguson et al, 2009; McCollum et al, 2011; So et al, 2011). Despite these promising outcomes, the mechanism of TGF-β3 action following injury is unclear, particularly with respect to cross-tissue variation in scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…Before concluding that TGF-β3 is ineffective, some technical aspects need to be further addressed. Because TGF-β3’s mechanism of action is through its inhibition of TGF-β1 and TGF-β2, some investigators feel TGF-β3 should be administered before injury [17, 18] and sustained through the remodeling phase of healing [19]. The rationale is that the initial cascade of cytokines involved in wound healing and scarring are triggered immediately after injury and present until the healing process is complete [10, 18].…”
Section: Discussionmentioning
confidence: 99%
“…A more relevant factor may be the degree of involved surface area. This model creates a larger injured surface area than in other studies on dermal scars, vocal cord injury, and buccal mucosal injury [17, 18, 21]. Larger areas of injury lead to prolonged exposure of fibrotic cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The use of TGF-β3 has also been effectively tested in animal models, where it was found to reduce fibrosis and scarring by decreasing TGF-β1/2 levels (Shah et al, 1995; O'Kane and Ferguson 1997; Ohno et al, 2012; Chang et al, 2013). However, similar to the clinical challenges observed with TGF-β1 and 2 specific antibodies, no significant mitigation of scar development could be observed with TGF-β3 in an international Phase III clinical trial (Renovo, 2011).…”
Section: Possibilities For Therapeutic Interventionmentioning
confidence: 99%